A persistência da memória na cidade contemporânea. Reabilitação de conjunto habitacional na Rua 5 de Outubro - Tomás Frias Ceitlin (2020)
Requalification. A broadly discussed term in architecture and, possibly, more relevant than imagined nowadays. Previously inhabited structures, with different meanings for those who once participated in its history, now face obsolescence due to the city's expansion logic. Without any use, part of the affective memory that contributes to the constitution of Oporto's singularity as a city is lost, and as a result, gives space to new buildings, frequently lacking aesthetical qualities and meaning. The present dissertation focuses on the architectonical project of requalification of eight bourgeois houses associated in a row, located in Rua de 5 de Outubro, in the city of Oporto. The process, which encompasses the building's chronologic trajectory since its conception until its present state of disregard, seeks to understand the reasons that led to this state, while also, hypothesizing new alternatives, in hopes to aid in the search of a new meaning through macro and micro territory reviews and also typology and construction analysis. This particular row housing typology, due to its scale and location, presents itself as an easy adaptable model, which could accommodate new uses while retaining its singular characteristics. In times where it's known that resources are finite, the building could be seen as one rather than a deadlock to be demolished, enhancing therefore the persistence of the memory in the contemporary city.